A low-loss integrally formed inductor powder, a preparation method and application thereof

CN122930714APending Publication Date: 2026-10-16SHENZHEN TOPSUN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611116385.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

为了满足低损耗的要求,通常需要对合金粉末进行包覆、钝化等处理,处理工艺往往步骤繁琐,且使用的辅料种类较多,成本较高,同时,在高频高磁通密度条件下,磁芯损耗较为严重

Benefits of technology

1、本发明中,通过优化钝化液配方和胶黏剂,在保证性能的前提下减少了添加剂的总种类和使用量,降低了原材料成本和工艺复杂性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930714A_ABST
    Figure CN122930714A_ABST
Patent Text Reader

Abstract

The application relates to a low-loss integrally-formed inductor powder and a preparation method and application thereof, and comprises the following steps: S1, mixing alloy powder and a dispersant solution, stirring and dispersing, and then drying to obtain pretreated powder; S2, mixing the pretreated powder and a passivation liquid, stirring, and then drying to obtain passivated powder; S3, mixing the passivated powder and a glue solution, stirring, granulating, baking, and sieving to obtain granulated powder; S4, adding a release agent to the granulated powder, uniformly mixing, and then performing die molding to obtain a green body of a magnetic ring; and S5, solidifying the green body of the magnetic ring, and performing heat treatment at 600 DEG C to 750 DEG C in a nitrogen-hydrogen mixed atmosphere containing 5% to 20% hydrogen. The application has the beneficial effect that by optimizing a passivation liquid formula and an adhesive, the raw material cost and process complexity are reduced, the performance of the powder is maintained, and the magnetic ring made of the powder exhibits lower magnetic core loss than traditional processes under the conditions of high frequency and high magnetic flux density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetic materials technology, specifically to a low-loss integrally molded inductor powder, its preparation method, and its application. Background Technology

[0002] Molded inductors are integral inductor components manufactured by embedding hollow coils into a mold, filling them with insulating magnetic powder, and then pressing and curing them. Compared with traditional assembled inductors, molded inductors have a fully enclosed structure, which can effectively avoid magnetic leakage and reduce electromagnetic interference between components. They also have advantages such as small size, high mechanical strength, and good reliability, and are used in high-frequency, high-power-density fields such as 5G communications, computers, automotive electronics, and artificial intelligence.

[0003] In existing technologies, the commonly used powders for integrally molded inductors are soft magnetic alloy powders such as Fe, Fe-Si, Fe-Ni, and Fe-Si-Al. To meet the requirements of low loss, the alloy powder usually needs to be coated and passivated. The processing steps are often complicated, and a variety of auxiliary materials are used, resulting in high costs. At the same time, under high frequency and high magnetic flux density conditions, the core loss is relatively severe. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this application proposes a low-loss integrally molded inductor powder, its preparation method, and its application. By optimizing the passivation solution formulation and adhesive, the cost of raw materials and the complexity of the process are reduced. While maintaining the various properties of the powder, the magnetic ring made from this powder exhibits lower core loss than that of traditional processes under high frequency and high magnetic flux density conditions.

[0005] The following is the technical solution of the present invention: a method for preparing low-loss integrally molded inductor powder, comprising the following steps: S1. Mix the alloy powder with the dispersant solution, stir and disperse, and then dry to obtain the pretreated powder; The amount of dispersant added is 0.2% to 1.0% of the alloy powder mass; S2. Mix the pretreated powder with the passivation solution, stir and dry to obtain passivated powder; The passivation solution contains a passivating agent and an organic solvent. The amount of passivating agent added is 0.1% to 2.0% of the alloy powder mass, and the amount of organic solvent used is 5% to 10% of the alloy powder mass. S3. The passivation powder is mixed with the adhesive solution, stirred, granulated, baked and sieved to obtain granulated powder; The adhesive solution contains an adhesive and an organic solvent, with the amount of adhesive added being 0.5% to 2.0% of the alloy powder mass. S4. Add a release agent to the granulated powder, mix evenly, and then mold to obtain a magnetic ring green body. The release agent is added at a rate of 0.1% to 0.5% of the granulated powder mass, and the molding pressure is 12 T / cm. 2 Up to 20T / cm 2 ; S5. The green magnetic ring is cured and heat-treated at 600°C to 750°C in a nitrogen-hydrogen mixed atmosphere containing 5% to 20% hydrogen.

[0006] In a preferred embodiment of the present invention, in S1, the alloy powder is Fe-Ni alloy powder; The Ni content is 45%-55%, and the O content is <0.19%, S content is <0.0025%, C content is <0.007%, with the balance being Fe.

[0007] In a preferred embodiment of the present invention, in S2, the passivating agent comprises a silane coupling agent and a phosphate.

[0008] In a preferred embodiment of the present invention, in S3, the adhesive is a composite adhesive of modified silicone resin and epoxy resin.

[0009] As a preferred embodiment of the present invention, in S3, the drying conditions are: baking at 80°C to 150°C for 60 to 150 minutes; and the mesh size of the sieve used for sieving is 80 to 300 mesh.

[0010] As a preferred embodiment of the present invention, in S4, the release agent is one or more of paraffin powder, hexagonal boron nitride, polyethylene glycol, and zinc stearate.

[0011] As a preferred embodiment of the present invention, in S5, the curing is performed by a stepped temperature increase curing method, including: The temperature is raised from room temperature to 60°C and maintained at that temperature. Reheat to 90℃ and maintain the temperature; Reheat to 120℃ and maintain the temperature; Finally, raise the temperature to 180℃ and maintain it.

[0012] A low-loss integral molded inductor powder is prepared by the aforementioned method for preparing low-loss integral molded inductor powder.

[0013] A magnetic ring is made from a low-loss integrally molded inductor powder by pressing, curing and heat treatment.

[0014] A molded inductor includes a magnetic ring and a coil wound on the magnetic ring.

[0015] The beneficial effects of this invention are: 1. In this invention, by optimizing the passivation solution formulation and adhesive, the total number and amount of additives used are reduced while ensuring performance, thereby reducing raw material costs and process complexity; 2. In this invention, the insulation uniformity and particle flowability of the powder are improved through optimized pretreatment, passivation and granulation processes. While maintaining the various properties of the powder, the magnetic ring made from the powder exhibits lower core loss than that of the traditional process under high frequency and high magnetic flux density conditions. Attached Figure Description

[0016] Figure 1 This is a flowchart illustrating the preparation method of the present invention. Detailed Implementation

[0017] To make the technical problems solved by the present invention, the technical solutions adopted, and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Example 1 like Figure 1 As shown, a method for preparing low-loss integrally molded inductor powder includes the following steps: S1. Mix the alloy powder with the dispersant solution, stir and disperse, and then dry to obtain the pretreated powder; The dispersant is added at a rate of 0.2% to 1.0% of the alloy powder mass, and the mixture is stirred using a planetary mixer.

[0019] The dispersant is selected from one or more of sodium hexametaphosphate, polyvinylpyrrolidone, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0020] S2. Mix the pretreated powder with the passivation solution, stir and dry to obtain passivated powder; The passivation solution contains a passivating agent and an organic solvent. The amount of passivating agent added is 0.1% to 2.0% of the alloy powder mass, and the amount of organic solvent is 5% to 10% of the alloy powder mass. The passivation solution is stirred evenly by a magnetic heating stirrer and then mixed with the powder, and then mixed again by a planetary mixer.

[0021] S3. The passivation powder is mixed with the adhesive solution, stirred, granulated, baked and sieved to obtain granulated powder; The adhesive solution contains an adhesive and an organic solvent. The amount of adhesive added is 0.5% to 2.0% of the alloy powder mass. The adhesive is a composite adhesive of modified silicone resin and epoxy resin. The organic solvent is acetone. The mixture is stirred in a mixer for no less than 40 minutes. When the moisture content of the powder is 15% to 25%, it is granulated using a granulator with a 50-80 mesh sieve. Then it is baked at a temperature of 80℃ to 150℃ for 60 to 150 minutes, and then sieved through a 80-300 mesh sieve.

[0022] S4. Add a release agent to the granulated powder, mix evenly, and then mold to obtain a magnetic ring green body. The granulated powder has a mesh size of 80 to 300 mesh, the release agent is added at a rate of 0.1% to 0.5% of the granulated powder mass, and the molding pressure is 12 T / cm. 2 Up to 20T / cm 2 The release agent is one or more of the following: paraffin powder, hexagonal boron nitride, polyethylene glycol, and zinc stearate.

[0023] S5. The green magnetic ring is cured and then heat-treated at 600°C to 750°C in a nitrogen-hydrogen mixed atmosphere containing 5% to 20% hydrogen.

[0024] Example 2 This embodiment provides a low-loss integrally molded inductor powder, which is prepared by any one of steps S1 to S3 in Embodiment 1.

[0025] Example 3 This embodiment provides a magnetic ring, which is made from the powder prepared in Embodiment 2 through pressing, curing and heat treatment.

[0026] Example 4 This embodiment provides a molded inductor, including: a magnetic ring prepared in Embodiment 3 and a coil wound on the magnetic ring.

[0027] Example 5 This embodiment provides a method for preparing a magnetic ring, comprising: using granulated powder obtained by any of the preparation methods in Embodiment 1, adding a release agent and molding it, followed by curing and heat treatment to obtain a magnetic ring.

[0028] Example 6 This embodiment is prepared based on the preparation method of Example 1, and includes the following steps: S10. Mix the alloy powder with the dispersant solution, stir and disperse, and then dry to obtain the pretreated powder. The alloy powder used is 1000g of Fe-Ni alloy raw powder, referred to as raw powder 1. Its Ni content is 50.04%, O content is 0.18%, S content is 0.002%, C content is 0.006%, and the balance is Fe. The particle size distribution of the iron powder is D50 to D90.

[0029] Weigh 8g of sodium hexametaphosphate as a dispersant and add 80g of deionized water to prepare a dispersion. Mix the dispersion with the alloy powder and stir using a planetary mixer at 300 rpm for 40 minutes to ensure uniform mixing. Then spread the mixture out and dry it in an oven at 80℃ for 2 hours. After drying, grind and disperse the powder.

[0030] S20. Mix the pretreated powder with the passivation solution, stir and dry to obtain passivated powder; Weigh out 5g of silane and 8g of zinc dihydrogen phosphate. First, dissolve the silane in 60g of ethanol and stir magnetically for 40 minutes; then quickly add the zinc dihydrogen phosphate and continue stirring for 5 minutes to obtain the passivation solution.

[0031] Mix the passivation solution with the pretreated powder and stir in a planetary mixer for 50 minutes. Remove the mixture and allow it to stand at room temperature to evaporate and dry.

[0032] S30. The passivation powder is mixed with the adhesive solution, stirred, granulated, baked and sieved to obtain granulated powder; Weigh 12g of modified silicone resin adhesive and epoxy resin composite glue, dissolve them in 80g of acetone, and stir magnetically for 60 minutes. Use a magnetic heating stirrer to stir magnetically at a speed of 300r / min and a temperature of 35℃ to prepare the adhesive solution.

[0033] The adhesive solution is added to the passivated powder and kneaded using a kneader. Once the solvent has partially evaporated and the material is in a moist, lumpy state, it is extruded and granulated through a 60-mesh sieve.

[0034] The wet granules were baked in an oven at 100°C for 120 minutes. After cooling, they were passed through a 150-mesh sieve to obtain dry granulated powder.

[0035] S40. Add a release agent to the granulated powder, mix evenly, and then mold to obtain a magnetic ring green body. Add 3g of zinc stearate as a release agent to the granulation powder, mix evenly in a mixer, weigh an appropriate amount of powder, place it in a mold, and press at 15T / cm. 2 The magnetic ring blank is formed under pressure.

[0036] S50. The green magnetic ring is cured, and then heat-treated at 680°C in a nitrogen-hydrogen mixed atmosphere containing 10% hydrogen. Place the green magnetic ring in an oven and cure it according to the following procedure: Curing process: from room temperature to 60℃ for 30 minutes, then hold at that temperature for 30 minutes. The temperature was raised from 60℃ to 90℃ in 30 minutes, and then kept warm for 30 minutes. The temperature was raised from 90℃ to 120℃ in 30 minutes, and then kept warm for 45 minutes. The temperature was raised from 120℃ to 180℃ in 45 minutes, held for 120 minutes, and then allowed to cool naturally.

[0037] The heating rate is 1℃ / min to 1.5℃ / min.

[0038] The cured magnetic ring was placed in a tube furnace with a mixed atmosphere of hydrogen and nitrogen in a volume ratio of 9:1, heated to 680°C at a rate of 3°C / min, held at that temperature for 7 hours, and then cooled to room temperature with the furnace to obtain a magnetic ring sample.

[0039] Comparative Example 1 This comparative example uses the same raw powder 1 as in Example 6. The difference is: In step S20, the passivation solution is replaced with a conventional phosphoric acid solution. In this comparative example, the amount of phosphoric acid added to the phosphoric acid solution is 1.0% of the powder weight, and the amount of acetone solvent is 8%.

[0040] The formulations and process parameters for steps S10, S30, S40, and S50 are consistent with those in Example 6, and control magnetic ring samples are prepared.

[0041] Example 7 In this embodiment, instead of using powder 1 from Example 6, powder 2 is used. Powder 2 and powder 1 have different Ni contents and different μ values. The magnetic ring sample is prepared using the same process as in Example 6.

[0042] Comparative Example 2 In this comparative example, instead of using powder 1 from Comparative Example 1, powder 2 was used. Powder 2 and powder 1 have different Ni contents and different μ values. The magnetic ring sample was prepared using the same process as in Comparative Example 1.

[0043] Example 8 In this embodiment, instead of using powder 1 from Example 6, powder 3 is used. Powder 3 and powder 1 have different Ni contents and different μ values. The magnetic ring sample is prepared using the same process as in Example 6.

[0044] Comparative Example 3 In this comparative example, instead of using powder 1 from Comparative Example 1, powder 3 was used. Powder 3 and powder 1 have different Ni contents and different μ values. The magnetic ring sample was prepared using the same process as in Comparative Example 1.

[0045] The initial permeability μ and core loss Pcv at different frequencies and magnetic flux densities were tested on the magnetic ring samples prepared in Examples 6, 7, and 8, as well as Comparative Examples 1, 2, and 3. The results are shown in Table 1.

[0046] Table 1 shows the test results of magnetic core loss.

[0047]

[0048] As shown in the table above, the magnetic rings prepared using the process of this invention in Examples 6, 7, and 8, compared with Comparative Examples 1, 2, and 3 using the traditional phosphoric acid passivation process, exhibit significantly reduced core loss Pcv under test conditions of 200kHz / 50mT, 500kHz / 50mT, and 1MHz / 50mT, while maintaining an essentially unchanged initial permeability μ. Particularly under the high-frequency condition of 1MHz / 50mT, the losses of the three powders were reduced by approximately 11.7%, 10.3%, and 19.9%, respectively, effectively verifying the excellent effect of the process of this invention in reducing high-frequency magnetic losses.

[0049] This invention optimizes the passivation solution formulation and adhesive, reducing the total types and amounts of additives used while ensuring performance, thereby lowering raw material costs and process complexity. Through optimized pretreatment, passivation, and granulation processes, the insulation uniformity and particle flowability of the powder are improved. While maintaining the various properties of the powder, the magnetic ring made from this powder exhibits lower core loss than that of traditional processes under high frequency and high magnetic flux density conditions.

[0050] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Clearly, those skilled in the art can make various alterations and variations to the invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of equivalents of the invention, the invention is also intended to include these modifications and variations.

Claims

1. A method for preparing powder for low-loss integrally molded inductors, characterized in that, Includes the following steps: S1. Mix the alloy powder with the dispersant solution, stir and disperse, and then dry to obtain the pretreated powder; The amount of dispersant added is 0.2% to 1.0% of the alloy powder mass; S2. Mix the pretreated powder with the passivation solution, stir and dry to obtain passivated powder; The passivation solution contains a passivating agent and an organic solvent. The amount of passivating agent added is 0.1% to 2.0% of the alloy powder mass, and the amount of organic solvent used is 5% to 10% of the alloy powder mass. S3. The passivation powder is mixed with the adhesive solution, stirred, granulated, baked and sieved to obtain granulated powder; The adhesive solution contains an adhesive and an organic solvent, with the amount of adhesive added being 0.5% to 2.0% of the alloy powder mass. S4. Add a release agent to the granulated powder, mix evenly, and then mold to obtain a magnetic ring green body. The release agent is added at a rate of 0.1% to 0.5% of the granulated powder mass, and the molding pressure is 12 T / cm. 2 Up to 20T / cm 2 ; S5. The green magnetic ring is cured and heat-treated at 600°C to 750°C in a nitrogen-hydrogen mixed atmosphere containing 5% to 20% hydrogen.

2. The method for preparing low-loss integrally molded inductor powder according to claim 1, characterized in that, In S1, the alloy powder is Fe-Ni alloy powder; The Ni content is 45%-55%, and the O content is <0.19%, S content is <0.0025%, C content is <0.007%, with the balance being Fe.

3. The method for preparing low-loss integrally molded inductor powder according to claim 1, characterized in that, In S2, the passivating agent includes a silane coupling agent and a phosphate.

4. The method for preparing low-loss integrally molded inductor powder according to claim 1, characterized in that, In S3, the adhesive is a composite adhesive of modified silicone resin and epoxy resin.

5. The method for preparing low-loss integrally molded inductor powder according to claim 1, characterized in that, In S3, the drying conditions are: baking at 80°C to 150°C for 60 to 150 minutes; the mesh size of the sieve used for sieving is 80 to 300 mesh.

6. The method for preparing low-loss integrally molded inductor powder according to claim 1, characterized in that, In S4, the release agent is one or more of the following: paraffin powder, hexagonal boron nitride, polyethylene glycol, and zinc stearate.

7. The method for preparing low-loss integrally molded inductor powder according to claim 1, characterized in that, In S5, curing is performed using a stepped temperature curing method, including: The temperature is raised from room temperature to 60°C and maintained at that temperature. Reheat to 90℃ and maintain the temperature; Reheat to 120℃ and maintain the temperature; Finally, raise the temperature to 180℃ and maintain it.

8. A low-loss integrally molded inductor powder, characterized in that, It is prepared by the powder preparation method for a low-loss integrally molded inductor according to any one of claims 1-7.

9. A magnetic ring, characterized in that, It is made from the low-loss integral molded inductor powder of claim 8 by pressing, curing and heat treatment.

10. A molded inductor, characterized in that, It includes a magnetic ring as described in claim 9, and a coil wound on the magnetic ring.